Richter modified sacrospinous colpopexy – surgical complications of first operations - Surkont, Grzegorz; Wlaźlak, Edyta; Stetkiewicz, Tomasz; Sobczuk, Anna; Krajewski, Paweł; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2005)
There are a lot of different surgical techniques utilized to repair symptomatic enterocele. Richter sacrospinous colpopexy is very popular. In the literature there are many modifications of this procedure. But there are not a lot of information about complications and learning curve. The aim of this study is analysis of problems and complications which can happen during first modified Richter operations and evaluation of peri- and and short-term postoperative results. Material and methods: Prospectively we evaluated first 80 procedures done by two gynecologic surgeons in women with symptomatic enterocoele II, III or Iv degree according to POP-Q test recommended by ICS. Because in all of these patients we found also cystocele and/or SUI I, II and III degree, all of them had urodynamic evaluation and cough test. Modified Richter operation was done according to technique recommended by prof. E. Petri (Germany). Results: During first 10 procedures of both surgeons there were problems in identifying sacrospinous ligament in 20-40% of cases. With gaining the experience technical problems occured much rare. During short-term observations we did not find negative influence of combining POP and SUI treatment procedures on results. Conclusions: 1. Providing modified Richter operation results with low incidence of complications, even during first procedures. 2. After doing about 20 operations, as a consequence of better visualisation the sacrospinous ligament, the time of operation was becoming shorter.